OP41 Birth Size and Mortality in Breast Cancer Patients. (17th September 2012) - Sovio, U; Jones, R; Koupil, I
Abstract : Background: Previous studies suggest that larger birth size is associated with a higher breast cancer incidence, but the few studies of birth measures and mortality in breast cancer cases have been inconclusive. The aim of this study was to investigate survival of women after breast cancer diagnosis (N=436) in the Uppsala Birth Cohort born in 1915–1929, who had detailed obstetric records available. Methods: Cox regression was used to calculate hazard ratios (HR) and their 95% confidence intervals (CIs) for death from any cause after a breast cancer diagnosis until the end of 2010. Cancer register diagnoses were available from 1958. The main exposures were birth measures: gestational age (GA), birth length (BL), and birth weight (BW) for GA. They were converted to standard deviation (SD) scores to ensure comparability of the effect sizes. Analyses were performed with and without adjustment for own adult socio-economic position (SEP) measured by education, occupation and income. Analyses were additionally adjusted for age at breast cancer diagnosis, decade of diagnosis, and age at first birth. Adjustment for family SEP at birth was considered but omitted since it did not affect the estimates and was not related to mortality after adjustment for other confounders. Results: In adjusted analyses, one SD increase in GA was associated with 7% (95% CI 2–12%) lower mortality and this association did not change after additional adjustments for BL or BW. There was no association between BL and mortality (adjusted HR=1.02 (0.91–1.16)). One SD increase in BW for GA was associated with 14% (1–29%) and 26% (9–46%) higher mortality without and with an additional adjustment for BL, respectively. Adjustment for SEP or other confounders did not substantially alter the estimates. Conclusion: Our results suggest that both low GA and high BW for GA predict a higher mortality in breast cancer cases. This study strengthens the current evidence that size at birth is related to breast cancer mortality as well as incidence. It also brings in new evidence of the inverse relationship between GA and breast cancer mortality that has not been reported before. The observed associations persisted after an adjustment for SEP, although breast cancer cases from lower SEP are known to have a poorer survival and also birth measures are socially patterned. Further studies are needed to investigate how the observed associations are mediated.